When climate crisis hits home: mental health of elderly with type 2 diabetes amidst floods in Brazil - Marcell Machado Cipolat; Lucas Strassburger Matzenbacher; Laura Gomes Boabaid de Barros; Ana Gabriela Rodrigues Haussen; Mariana Kude Perrone; Helena Toniazzi Uchôa; Bianca Gomes Corrêa; Vicenzo Gheno; Frederico Ludwig da Costa; Gabriela Heiden Telo (Diabetology & Metabolic Syndrome)
Abstract Background Climate change has increased the frequency of natural disasters, challenging society in various aspects. Individuals living with chronic diseases are particularly vulnerable due to their constant need for medical care. This study aimed to investigate the impact of the unprecedented floods that hit Brazil in 2024 on the mental health of elderly with diabetes. Methods This is a cross-sectional study involving outpatient elderly individuals with type 2 diabetes in Southern Brazil. Participants were stratified into two groups according to the impact their residences suffered from the floods (directly vs. non-directly impacted). The study outcome was mental distress, assessed using the Self-Report Questionnaire-20 (SRQ-20). Analyses of covariance and multivariable logistic regression were used for between-group comparisons. Results A total of 80 elderly individuals were included, with a mean age of 72.5 ± 5.5 years old. Among the participants, 67.5% were women, and 57.5% were white. Fifty individuals were directly affected by the floods, while 30 were non-directly impacted. When compared, SRQ-20 scores were significantly higher in the directly impacted group, with an adjusted mean difference of 2.56 (95% CI: 0.42–4.70; p = 0.020), indicating higher mental distress among those directly impacted. Additionally, the prevalence of positive screening for mental distress was higher among those directly impacted by the floods (58% vs. 30%; adjusted OR = 4.16 [95% CI = 1.40-12.31], p = 0.010). Conclusions Our findings highlight the significant prevalence of mental distress among those directly impacted by climate disasters, underscoring the need for public policies and strategies focused on mental health during and after such disasters.